Peri- and Postoperative Treatment with the Interleukin-1 Receptor Antagonist Anakinra Is Safe in Patients Undergoing Renal Transplantation: Case Series and Review of the Literature - Mulders-Manders, Catharina M.; Baas, Marije C.; Molenaar, Femke M.; Simon, Anna (Frontiers in Pharmacology, 2017)
In patients undergoing solid organ transplantation, the presence of an interleukin-1 (IL-1) driven disease may require the addition of IL-1 inhibiting drugs to the standard immunosuppressive regimen to protect against inflammation and negative graft outcome. Three patients undergoing renal transplantation were treated perioperatively with the interleukin-1 receptor antagonist anakinra. Kidney function increased rapidly in all three and the only complications seen were minor infections. In vitro studies report associations between serum and urinary levels of IL-1β and IL-1 receptor antagonist and negative graft outcome, and studies in animals and two small human trials illustrate a possible protective effect of anti-IL-1 therapy after solid organ transplantation. Peri- and postoperative use of anakinra is safe and effective in patients undergoing renal transplantation.